Organización de un sistema de suministro y distribución de una empresa de catering - Alban, Enrique (2009)
The competitiveness is a concept, although relatively new, it’s necessary to apply it to every single yield activity of the country, in order, for the country, to be able to join today’s globalize World. This Project seeks to determine the adequate logistics system to improve the delivery of prepared foods that have this company, so, in that way, the company could minimize the time and distance traveled in de delivery of service to each of its points. We will determine the feasibility in the evaluation of the network, to have, in that way, a better market coverage and customer service. We will present a preliminary analysis of the present situation that will help to observe the behavior of the variables in relation to the distribution of routes in each sector. As a computational tool to solve this model, we chose the program model Routseq.